2018
DOI: 10.1111/den.13058
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after endoscopic ultrasound‐guided ethanol‐lipiodol ablation of small pancreatic neuroendocrine tumors

Abstract: We found that EUS-ELA was a safe and effective alternative option in the management of PNET <2.0 cm in diameter; 60% of patients achieved complete ablation. Lipiodol retention within tumor may be a useful early predictor of treatment effectiveness. Trial registered at ClinicalTrials.gov (NCT 01902238).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
2
41
2
1
Order By: Relevance
“…Therefore, considering the adverse events, ≤2.0 mL ethanol per session seems to be better for avoiding adverse events. Choi et al . reported that the presence of a capsule around the tumor was a significant factor influencing the success of complete ablation ( P = 0.008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, considering the adverse events, ≤2.0 mL ethanol per session seems to be better for avoiding adverse events. Choi et al . reported that the presence of a capsule around the tumor was a significant factor influencing the success of complete ablation ( P = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on treatment with EUS-guided ethanol injection have described the amount of ethanol as ranging from 0.3 to 8.0 mL. [3][4][5][6][7] Park et al 3 reported the outcomes of 11 patients with 14 tumors, and a median 1.6 (range: 0.5-3.8) mL of ethanol per session was used for tumors of a median 12.2 (range 8-19) mm in size. Median total amount of ethanol for each tumor was thus 2.5 (range 0.5-7) mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several case reports and a small case series of EUS‐EA have been reported, showing a success rate of 50–100% if success rate is defined as symptom disappearance in patients with functional PNEN (F‐PNEN) and radiological evidence of complete tumor ablation in patients with NF‐PNEN …”
mentioning
confidence: 99%